Digital Forensic Governance Strategy in Indonesia to Realize The Credibility of Accountable and Efficient Public Law Enforcement Agencies - Surya Dwi Putra; Stanislaus Riyanta (International Journal Labs, 2025)
The rapid advancement of digital technology has made the use of digital forensic equipment essential for law enforcement in Indonesia, particularly by state institutions and government agencies. In today's digital era, nearly all human activities involve digital technology, necessitating the use of digital devices. When unlawful acts occur within the territory of Indonesia, digital forensic tools are vital for extracting data from devices, which can be utilized as evidence to uncover legal facts. This research aims to formulate strategies for managing digital forensics in an efficient, accountable, and credible manner. A qualitative approach was used, employing the literature study method to gather relevant data from various sources. The findings highlight the importance of establishing clear protocols for the use of digital forensic equipment, ensuring the accuracy and legality of data extraction. Additionally, the study emphasizes the need for proper training, certification, and standardization of practices among law enforcement agencies to enhance credibility and accountability. The research contributes to the development of strategic frameworks for managing digital forensics in Indonesia, providing a foundation for improving law enforcement practices in the digital age.